(untitled) (Biological Sciences - PJSIR, 2002)
Indium telluride thin films are prepared by thermal evaporation technique onto glass substrate held at room temperature at deposition pressure 2xl 0-4 Pa. Electrical studies of the films annealed in air at 400 K shows semiconducting behaviour. Thickness dependent electrical conductivity , activation energy, aging effect are also being investigated. Activation energyis found to decrease with film thickness. Thickness dependent conductivity is found to follow Fuchs-Sondheimer size effect theory. The Hall and thermoelectric measurements show that the films are p-type semiconductor having high carrier concentration ofthe order 1018/cm3.